Learning Model with LMS as an Innovation to Facilitate the Implementation of Learning from Home - Purba, Ramen Antonov; Munthe, Rikawati Ginting; Ginting, Kalvin (Jurnal Pendidikan Indonesia, 2022)
Learning from home occurs due to the Covid-19 pandemic. Even if it is done from home, learning quality must be maintained. This study aims to analyze the effect of combining learning models with LMS to increase student learning independence and outcomes. This research combines LMS media, in this case, Schoology, blended learning model, and guided inquiry learning model in one package. The study used a pretest and posttest control group design. The control group used google classroom and google meet. The experimental group used a combination of the learning model with LMS. It was found that the average quality of the learning independence of the experimental group was higher than the mean of independence in the learning of the control group. Likewise, the learning achievement of the experimental group obtained a value greater than the average learning achievement of the control class. The combination of learning models with LMS effectively increases independence in learning and student learning outcomes in learning situations from home.